The teaching of History with the museum: educational practices in reflective processes - Costa, Júlio César Virgínio da (Revista Crítica Histórica, 2017)
In this text we present reflections on the resonance of an educational practice in the teaching of History developed in a museum of the city of Belo Horizonte in the teaching of the Prehistory of Brazil. This educational and memory practice is understood as part of a process begun before the visit and that continues after the end of the visit, that is, the analyzes are connected to the dynamics established in the times that involve a museum visitation, that cross that environment and in dialogue Constant with the classroom. The effort undertaken aims to understand how the resonance of this educational practice mobilize several aspects that directly can contribute to another grammar of teaching history and memory teaching in museum environments and also to an understanding of continuing teacher education.